Penghambatan Oksidasi Lipid Minyak Ikan Cakalang (Katsuwonus pelamis) Oleh Air Jahe (Zingiber officinale var. rubrum) Selama Penyimpanan Dingin - Ilevena Rolima Josef; Ardi Kapahang; Dokri Gumolung (Jurnal Kimia Fullerene, 2019)
Fish is one of the main foods for humans that are rich of proteins, fatty, and minerals that are good for health. Unsaturated fatty acids are very easily oxidized by the presence of catalysts such as oxygen, heat, light, and the presence of metals. Ginger contains antioxidants which can inhibit oxidation of fat or oil. This study aims to inhibit fat oxidation of skipjack fish with the addition of ginger. Skipjack fish soaked in ginger water with a concentration of 10%, 20%, 30% and the control, then saved for 0, 2, 4 days. The fish was extracted by the wet rendering method and then analyzed with 2 parameters, peroxide value and free fatty acids with the titration method. The best concentration in inhibiting lipid oxidation of skipjack fish is at a concentration of 10% and 30%. The peroxide value of cakalang oils is still below the IFOS standard of 3.75 meq O2/kg and the percentage of free fatty acids is still below the standard of 1.5%